Electrochemical stability of (La, Sr)CoO3−δ in (La, Sr)CoO3−δ/(Ce, Gd)O2−δ heterostructures. Issue 6 (28th January 2019) - dos Santos-Gómez, Lucía; Sanna, Simone; Norby, Poul; Pryds, Nini; Losilla, Enrique R.; Marrero-López, David; Esposito, Vincenzo
Abstract : A modulated coherent (La, Sr)CoO3− δ /(Ce, Gd)O2− δ heterostructure is characterized for the first time for its electronic and chemical properties. Abstract : A modulated coherent (La, Sr)CoO3− δ /(Ce, Gd)O2− δ heterostructure is characterized for the first time for its electronic and chemical properties. 2D-multilayer architectures are deposited on NdGaO3 (110) single crystal substrate by pulsed laser deposition, resulting in epitaxial structures with in-plane lattice rotation that, via the metal oxides' interfaces, induces mutual structural rearrangements. Our results show that (La, Sr)CoO3−d thin films of 10–100 nm are chemically unstable when exposed to air at 600 °C during electrical cyclic stress-tests. Conversely, improved stability is achieved confining LSC in the nanometric heterostructure. Remarkably, the chemical stabilization occurs without compromising substantially the electrical properties of the LSC component: the heterostructures show unexpected electrical behaviour with dominant electronic contributions, fast conductivity and mixed ionic-electronic properties, depending on the number of interfaces and the nano-scaled layers.